Deoxygenation of amine N-oxides using gold nanoparticles supported on carbon nanotubes1. Issue 63 (10th July 2015) - Donck, Simon; Gravel, Edmond; Shah, Nimesh; Jawale, Dhanaji V.; Doris, Eric; Namboothiri, Irishi N. N.
<x xml:space="preserve">Abstract</x> Carbon nanotube-supported gold nanoparticles were found to be potent catalysts in the mild deoxygenation of amine N-oxides.